The Application of Solution-Focused Brief Therapy (SFBT) in Islamic Counseling to Address Psychological Crises in Young Mothers After Divorce - Rahayu, Puji; Nurjannah, Nurjannah; Perkasa, Adrian (Al Musyrif: Jurnal Bimbingan dan Konseling Islam, 2025)
Divorce can trigger a sense of life disorientation and difficulties in fulfilling the role of a single parent. Using the Solution-Focused Brief Therapy (SFBT) approach, which emphasizes practical solutions and self-empowerment, counselors assist clients in recognizing their strengths, planning concrete steps to improve their lives, and accepting destiny with patience and sincerity in accordance with Islamic teachings. This study aims to examine the application of SFBT in Islamic counseling as an effort to address the psychological crisis experienced by young mothers after divorce. A case study method was employed, involving five counseling sessions. Data were collected through interviews, observations, and counseling notes, and were analyzed thematically. The findings indicate that the application of SFBT in Islamic counseling is effective in helping clients cope with psychological crises, focus on solutions, and enhance emotional well-being and their role as mothers. In conclusion, the SFBT approach in Islamic counseling can empower young divorced mothers to overcome life challenges and improve the quality of their personal and family life. The contribution of this study lies in integrating the modern psychotherapeutic approach of SFBT with Islamic spiritual values, demonstrating its effectiveness in the cultural and religious context of Indonesian society. These findings provide new insights for practitioners of Islamic counseling and psychotherapy regarding the importance of integrating strength-based and faith-oriented approaches in supporting clients through life crises. Furthermore, this research enriches the literature on Islamic counseling with a practical approach relevant for guiding women after divorce.